2021
DOI: 10.15376/biores.16.1.1373-1381
|View full text |Cite
|
Sign up to set email alerts
|

Models to estimate longitudinal compressive strength of Brazilian hardwood based on apparent density

Abstract: As wood is an orthotropic and natural material, there are several properties required for its use in civil construction. The apparent density has been used to estimate physical and mechanical properties of wood, as it is easy to determine experimentally, unlike other determinations, which involve the use of equipment available only in large research centers. Using the Brazilian standard ABNT NBR 7190 and linear and non-linear regression models, this research aimed to evaluate their accuracy in estimating the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…It is worth noting that the average values of the properties (ρap,12% and fc0), as well as the resistance classes categorized here, are in accordance with those obtained previously PEER-REVIEWED ARTICLE bioresources.com by Jesus et al (2015), Dias et al (2019), Duarte et al (2020), andLahr et al (2021).…”
Section: Resultssupporting
confidence: 91%
“…It is worth noting that the average values of the properties (ρap,12% and fc0), as well as the resistance classes categorized here, are in accordance with those obtained previously PEER-REVIEWED ARTICLE bioresources.com by Jesus et al (2015), Dias et al (2019), Duarte et al (2020), andLahr et al (2021).…”
Section: Resultssupporting
confidence: 91%
“…However, performing this type of test also requires the use of unique equipment that is often costly. In this context, several studies have shown that it is possible to estimate a property that is difficult to obtain through another that is more easily obtained by means of regression models with significant adjustments (Almeida et al 2014;Wolenski et al 2020;Lahr et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of these tests require the use of specific equipment that is only found in large research centers. This fact makes characterizations of this nature difficult, given the scarcity of laboratories of this magnitude in Brazil [7]. Due to this scarcity, the standards establish numerical correlations that allow the determination of mechanical properties through mathematical models, e.g., Equations ( 1)-(3) of NBR 7190 [6], where f c0,k is the characteristic fiber parallel compressive strength, f t0,k the characteristic fiber parallel tensile strength, and f m,k the characteristic flexural tensile strength.…”
Section: Introductionmentioning
confidence: 99%